Awareness, Perceptions, and Barriers Related to Orthodontic Treatment: A Cross-Sectional Survey in the Indian Population - Narkhede, Sameer; Shetty, Karthick D; Sonawane, Sushma; S Patil, Susmit; Gadhiya, Nitin Dinesh; Singh, Rakesh (Journal of Neonatal Surgery, 2025)
Introduction:Orthodontic treatment plays a crucial role in correcting malocclusion and improving oral function, aesthetics, and quality of life. Despite advances in orthodontics, a gap persists between the availability of treatment and its uptake, particularly in developing countries like India. Limited awareness, misconceptions, and perceived barriers often delay or prevent individuals from seeking timely care. The present cross-sectional study aimed to assess the awareness, perceptions, motivations, and barriers related to orthodontic treatment among a diverse Indian population and examine their associations with age and gender. Materials and Methods:A questionnaire-based survey was conducted among 365 participants aged 12 years and above. The survey was administered electronically through social media platforms using a structured Google Form. The questionnaire included demographic information, general awareness, treatment motivations, knowledge and misconceptions, and barriers to orthodontic care. Responses were analyzed using descriptive statistics and Chi-square tests to assess associations with age groups and gender, using SPSS v26.0. Results:Most respondents were aware of orthodontic treatment (87.7%) and recognized its esthetic and functional benefits. However, detailed knowledge, such as correct treatment timing and scope, varied significantly with age (p < 0.05) but not gender. Aesthetic concerns were the primary motivation (28%), while functional reasons were less cited. The most common barriers were lack of perceived need (33.4%), time constraints (16.7%), and social discomfort with braces (14%). Social acceptance was a more frequent concern among females (p = 0.045) and younger age groups. Conclusion:While general awareness of orthodontics is high, detailed knowledge remains inconsistent, and misconceptions persist. Age influences both awareness and perceived need, suggesting that age-targeted educational strategies, especially among youth, are essential to improve orthodontic literacy and access.